Prevention programmes including Nordic exercises to prevent hamstring injuries in football players (PEDro synthesis) - Oliveira Almeida, M.; Maher, C. G.; Saragiotto, B. T. (British Journal of Sports Medicine, 2018)
Background: Hamstring injuries are the most common non-contact injuries in sport1 and account for 40% of muscle injuries in football,2 where up to one-third recur the following season.3-5 The rehabilitation of players with hamstring injuries usually lasts more than a month, restricting the athlete`s performance and causing a financial impact on clubs.3 4 6 The Nordic hamstring (NH) exercise is a promising option to decrease the risk of hamstring injuries in athletes. However, results of randomised controlled trials have been conflicting.6-8 Aim: The aim of this review was to assess the effectiveness of injury prevention programmes that included NH exercise on reducing the incidence of hamstring injuries among football players.